AN ANALYSIS OF STUDENTS’ SPEAKING FLUENCY AT THE FIRST GRADE OF MADRASAH ALIYAH MASMUR PEKANBARU - Norliyang Bilianti; Nuardi (State Islamic University of Sultan Syarif Kasim Riau, 2026)
This study aimed to identify the level of speaking fluency of first grade students at Madrasah Aliyah Masmur Pekanbaru. The research employed a descriptive quantitative design and was conducted on 28 July 2025 at Madrasah Aliyah Masmur Pekanbaru. The population of this study consisted of 18 students from one class, and total sampling was applied. data were collected through a speaking test. The findings showed that the speaking fluency of the first-grade students at Madrasah Aliyah Masmur Pekanbaru was at Level 3 (Good), with an average score of 52.1 across all fluency measures, namely Speech Rate (SR), Pause Rate (PR), Disfluent Syllables (DS), and Mean Length of Run (MLR). Furthermore, 50% of the students (9 students) were classified at Level 3 (good), while the remaining 50% (9 students) were at Level 2 (intermediate).